With versus without bone grafts for operative treatment of displaced intra-articular calcaneal fractures: A meta-analysis. (November 2018) - Zheng, Wenhao; Xie, Linzhen; Xie, Huanguang; Chen, Chunhui; Chen, Hua; Cai, Leyi
Abstract: Purpose: This meta-analysis aimed to investigate the effectiveness of operative treatment of intra-articular calcaneal fractures with bone grafts versus without bone grafts. Methods: The electronic literature database of Pubmed, Embase, and Cochrane library were searched in April 2018. The data on Böhler angle, Gissane angle, calcaneal width, calcaneal height, AOFAS hindfoot scores and complications (including wound edge necrosis, wound infection, deep infection, hematoma and sural nerve injury) were extracted. The Stata 14.0 software was used for the meta-analysis. Results: Nine studies including 6 RCTs and 3 retrospective cohort studies met our inclusion criteria. This meta-analysis showed that there was no significant difference between the two groups regarding the Böhler angle (P = 0.44), Gissane angle (P = 0.06), calcaneal width (P = 0.09) and calcaneal height (P = 0.44) postoperatively and at the last follow-up. However, the bone graft group had significantly higher AOFAS scores than the non-bone graft group (P < 0.05). No significant difference was found between the two groups in complications (P = 0.63). Conclusion: This meta-analysis suggested that operative treatment of intra-articular calcaneal fractures with bone grafts achieved better AOFAS scores than the non-bone graft group. The two groups had similar results in Böhler angle, Gissane angle, calcaneal width and calcaneal height. No increased risk of postoperative complications was identified. More RCTs are required for further research. Highlights: This is the first meta-analysis on bone grafts versus without bone grafts for displaced intra-articular calcaneal fractures. The meta-analysis suggested that bone graft group achieved better AOFAS scores than the non-bone graft group. No increased risk of postoperative complications was identified in the bone graft group.